(untitled) (Aletria: Revista de Estudos de Literatura, 2019)
Major critics and philosophers of the Age of Theory (1965-1980) developed as an alternative to the hegemonic practice of interpretation the study of a poetics that, by rigorously describing the mechanisms of meaning production, would contribute to make hermeneutic practices more precise. Partially discarded as of little relevance, these studies offered, nevertheless, relatively important contributions to the development of new forms of understanding literary texts not restricted to the traditional hermeneutic practice. Agamben’s reading of Melville’s tale, Bartleby, the Scrivener, forcefully illustrates one of these new forms of understanding and the possible problems related to it.